Keeping the Spirits Up: The Effect of Teachers’ and Parents’ Emotional Support on Children’s Working Memory Performance - Vandenbroucke, Loren; Spilt, Jantine; Verschueren, Karine; Baeyens, Dieter (Frontiers in Psychology, 2017)
Working memory, used to temporarily store and mentally manipulate information, is important for children’s learning. It is therefore valuable to understand which (contextual) factors promote or hinder working memory performance. Recent research shows positive associations between positive parent-child and teacher-student interactions and working memory performance and development. However, no study has yet experimentally investigated how parents and teachers affect working memory performance. Based on attachment theory, the current study investigated the role of parent and teacher emotional support in promoting working memory performance by buffering the negative effect of social stress. Questionnaires and an experimental session were completed by 170 children from grade 1 to 2 (Mage= 7 years 6 months, SD = 7 months). Questionnaires were used to assess children’s perceptions of the teacher-student and parent-child relationship. During an experimental session, working memory was measured with the Corsi task backwards (Milner, 1971) in a pre- and post-test design. In-between the tests stress was induced in the children using the Cyberball paradigm (Williams et al., 2000). Emotional support was manipulated (between-subjects) through an audio message (either a weather report, a supportive message of a stranger, a supportive message of a parent, or a supportive message of a teacher). Results of repeated measures ANOVA showed no clear effect of the stress induction. Nevertheless, an effect of parent and teacher support was found and depended on the quality of the parent-child relationship. When children had a positive relationship with their parent, support of parents and teachers had little effect on working memory performance. When children had a negative relationship with their parent, a supportive message of that parent decreased working memory performance, while a supportive message from the teacher increased performance. In sum, the current study suggests that parents and teachers can support working memory performance by being supportive for the child. Teacher support is most effective when the child has a negative relationship with the parent. These insights can give direction to specific measures aimed at preventing and resolving working memory problems and related issues.